The Elements of Botany - Jussieu, Adrien de (Cambridge University Press, 1849)
The author of pioneering works on the plant families Euphorbiaceae and Malpighiaceae, French botanist Adrien de Jussieu (1797–1853), from a famous family of scientists, became professor of botany at the Paris Museum National d'Histoire Naturelle in 1826. The author of several specialised monographs, he is best known for his Botanique: Cours élémentaire d'histoire naturelle (1842), an exhaustive introduction to botany originally intended for use in French schools. This much acclaimed book went through twelve editions between 1842 and 1884, and was translated into many languages. This English translation, completed while he was still an Oxford student by the young British botanist James Hewetson Wilson (1826–50), was first published in 1849. It contains additional descriptions of the different systems and structures that clarify de Jussieu's terminology, as well as an appendix on geology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)